Efeitos da alimentação com restrição de tempo em comparação a outras estratégias dietéticas isocalóricas sobre as percepções subjetivas relacionadas a ingestão alimentar em adultos com sobrepeso ou obesidade: revisão sistemática de ensaios clínicos randomizados - Silva, Amarilis Dias da (2023)
Introduction: Intermittent fasting, specifically time-restricted eating (TRE), has shown promise in treating obesity. However, adherence to TRE is associated with diverse side effects on participants' subjective food perceptions, such as hunger, fullness, and satisfaction, which may impact outcomes. It is still unclear whether these effects are attributable to the TRE protocol itself or the caloric restriction imposed by its intervention. Objective: To conduct a systematic review of randomized controlled trials (RCTs) investigating the effects of TRE compared to other isocaloric dietary strategies on hunger levels and other subjective perceptions that may influence food intake in overweight or obese adults. As secondary outcomes, we also aimed to examine the impact of TRE on weight loss, changes in glycemic and lipid profiles, and alterations in body composition (lean mass and fat mass percentage). Methods: This review was registered in PROSPERO (CRD42021279863), and we employed the PICO strategy (P: overweight/obese adults, I: TRE fasting, C: isocaloric dietary strategy, O: subjective food perceptions) to guide our search and study selection. Exclusion criteria were determined by non-compliance with the PICO criteria. We searched major databases (PubMed, Medline, Embase, Lilacs and Cochrane Library) and grey literature (Opengrey and Google Scholar) without language or time restrictions until November 2021. We utilized the Rayyan software for study importation and screening. Data extraction was performed after a comprehensive reading of eligible articles, following PRISMA and Cochrane Handbook for Systematic Reviews of Interventions guidelines. Cochrane Review Manager 5.3 software was used for meta-analysis. Sensitivity analysis was conducted for studies classified as having a high risk of bias. Results and Discussion: Out of a total of 12,519 identified articles, we included nine studies for quantitative and qualitative analyses. Meta-analyses of primary outcomes comprised three reports, while meta-analyses of secondary outcomes comprised six. Our results showed that TRE led to an increase in hunger (MD 2.04, 95% CI 1.44-2.63; I²=0%) and higher levels of fullness (MD 0.99, 95% CI 0.69-1.29, I²=0%) compared to the isocaloric control group. The other subject perceptions evaluated qualitatively due to insufficient data or a minimum number of studies for meta-analysis (such as satisfaction, desire to eat, quantity of food, anxiety, emotional eating, mood, and uncontrolled eating) seem to be neutral between the TRE and control groups regarding other subjective perceptions. Meta-analyses of secondary outcomes also revealed no significant differences between the groups. Conclusion: Our findings indicate that TRE resulted in increased hunger and fullness compared to the control group. However, the scarcity of randomized clinical studies on TRE evaluating subjective perceptions influencing food intake does not provide robust clinical evidence supporting TRE as a preferred nutritional strategy for obesity treatment adherence. Therefore, further studies are warranted on this topic.